BY THE EXPERIENCE OF FOREIGN INTERNSHIP AMONG RUSSIAN STUDENTS’ OF CIVIL ENGINEERING DEPARTMENT OF IZHSTU AT BRNO UNIVERSITY OF TECHNOLOGY (2013) - Valery P. Grahov; Yulia G. Kislyakova (Образование и наука, 2015)
The aim of the study is to investigate the possibilities of foreign internships among Russian students. Methods. The methods involve general-scientific methods of theoretical research – analysis and synthesis. Results. The article is devoted to the analysis of foreign internships of Civil Engineering Department of Kalashnikov Izhevsk State Technical University in foreign universities for a specific period of time. The authors analyze the entry of Russian students into the European educational process. Additionally, the authors describe the educational process of training among Russian students of the Industrial and Civil Construction Department in Brno University of Technology. The training is conducted in accordance with the project of the European Union «Lifelong Learning Programme», which involves some non-profitable projects of foreign exchange of students and teachers; e.g. Erasmus Mundus, that is accessible more or less for all universities all over the world. A brief assessment of teaching subjects in the Czech University is given. The concept of students’ foreign internships as a part of preparation of intended graduates with a degree in «Construction» is extended. Evident, current and future advantages and benefits of such foreign internship projects are noted. Scientific novelty and practical significance. The research findings include the developed recommendations for students’ internship organization in foreign universities.